DETERMINAN PERILAKU PEMERIKSAAN PAYUDARA SENDIRI (SADARI) PADA WANITA USIA SUBUR DI KELURAHAN SIMPANG TIGA PEKANBARU TAHUN 2017 - zulmeliza meliza rasyid; Yuni Kristiani Siboro; Alhidayati Alhidayati; Syukaisih Syukaisih (Jurnal Kesehatan Komunitas, 2020)
Self breast examination (BSE) is a self-examination of the breast to detect any abnormalities in the breast. BSE is important for women, while in Pekanbaru area only 15.1% and those who do BSE in the Simpang Tiga Village area are 17.9% and one of them has died of breast cancer and is still less than the National standard 50% is not as expected do BSE. This study aims to determine the description and determinants of BSE on WUS in Simpang Tiga Pekanbaru Village in 2017. The type of this research is quantitative analytic with Cross Sectional research design conducted in June-July in the 2017 Simpang Tiga Pekanbaru Village. The sample is WUS located in Simpang Tiga Village. Inclusion Criteria WUS who are willing to be respondents aged 20-45 years, WUS who are not pregnant and breastfeeding, WUS exclusion criteria do not suffer from tumors or cancer, illness or disability during the study. The sampling technique used is quota sampling. The measuring instrument used is a questionnaire. Data analysis for bivariates using the Chi-Square test. The proportion of BSE in WUS in Simpang Tiga Village that conducts BSE is 22.9%. The results showed that there was a relationship between WUS who were not married (PRR = 1,240; 95% CI = 1,027-1,497), lack of self-awareness (PRR = 1,245; 95% CI = 1,036-1,496), family history of cancer (PRR = 1,895; 95% CI = 1,028-3,491), did not get the source of information (PRR = 1,250; 1,022-1,528), health workers (PRR = 1,485; 1,138-1,940) to WUS who did not do BSE. It is hoped that health workers at the Simpang Tiga Village Health Center will further improve their existing health promotion by training health workers as well as health cadres on the procedures for conducting BSE in accordance with the procedure, in order to provide information on the importance of conducting BSE to WUS in Simpang Tiga Village